Identifier les besoins en éthique professionnelle enseignante : une recension des écrits - Point, Christophe; Legault, Alexis (Canadian Journal of Education/Revue canadienne de l’éducation, 2025)
This study presents a review of the scientific literature concerning the professional ethics needs of teachers, specifically elementary school teachers in Quebec. Based on the “Quebec” conceptual framework of professional ethics for teachers and an appropriate and presented review methodology, we identify 61 academic writings, published between 2003 and 2021, that discuss these needs (i.e., the resources that teachers lack to respect a desirable professional ethics). The first part of this article presents the results of this review. The second part discusses the difficulty of developing an adequate conceptual framework to analyze the diversity and specific details of the identified needs.